Experimental PVC Material Challenge in Subjects with Occupational PVC Exposure - Tuomainen, Anneli; Stark, Harri; Seuri, Markku; Hirvonen, Maija-Riitta; Linnainmaa, Markku; Sieppi, Anne; Tukiainen, Hannu (Environmental health perspectives, 2006)
Background: Polyvinyl chloride (PVC) materials have been linked to asthma in several epidemiologic studies, but the possible causal factors remain unknown. Participants: We challenged 10 subjects experimentally to degraded PVC products under controlled conditions. All of the subjects had previously experienced respiratory symptoms suspected to be caused by this kind of exposure in their work place. Five subjects had doctor-diagnosed asthma. Methods: The subjects were exposed to degraded PVC material in an exposure chamber; a challenge with ceramic tile was used as the control test. We followed exhaled nitric oxide, nasal NO, lung functions, cytokines [tumor necrosis factor-α (TNF-α), interleukin-4 (IL-4), IL-6, and IL-12] and NO in nasal lavage fluid (NAL) during and after the exposures. We also measured 2-ethylhexanol in exhaled breath samples and NAL. Results: On the morning after the PVC exposure, subjects reported respiratory tract symptoms significantly more often than they did after the control test (50% vs. 0%, respectively; p = 0.029; n = 10). We did not detect any changes in lung functions or levels of exhaled NO, nasal NO, or NO in NAL after PVC challenge compared with the control test. Cytokine levels increased after both exposures, with no statistically significant difference between situations. All of the exhaled breath samples collected during the PVC exposure contained 2-ethylhexanol. Conclusions: PVC flooring challenge can evoke respiratory tract symptoms in exposed subjects. Our results do not support the hypothesis that PVC materials themselves evoke immediate asthmatic reactions. The chamber test used is well suited to this type of exposure study.